A multi-species cluster of GES-5 carbapenemase producing Enterobacterales linked by a geographically disseminated plasmid - Ellington,MJ; Davies,F; Jauneikaite,E; Hopkins,KL; Turton,JF; Adams,G; Pavlu,J; Innes,AJ; Eades,C; Brannigan,ET; Findlay,J; White,L; et al. (Clinical Infectious Diseases, 2020)
BACKGROUND: Early and accurate treatment of infections due to carbapenem-resistant organisms is facilitated by rapid diagnostics but rare resistance mechanisms can compromise detection. One year after a GES-5 carbapenemase-positive Klebsiella oxytoca infection was identified by whole genome sequencing (WGS) (later found to be part of a cluster of three cases), a cluster of 11 patients with GES-5-positive K. oxytoca was identified over 18 weeks in the same hospital.METHODS: Bacteria were identified by MALDI-TOF, antimicrobial susceptibility testing followed EUCAST guidelines. Ertapenem-resistant isolates were referred to Public Health England for characterization using PCR detection of GES, pulse-field gel electrophoresis (PFGE) and WGS for the second cluster.RESULTS: The identification of the first GES-5 K. oxytoca isolate was delayed, being identified on WGS. A GES-gene PCR informed the occurrence of the second cluster in real-time. In contrast to PFGE, WGS phylogenetic analysis refuted an epidemiological link between the two clusters; it also suggested a cascade of patient-to-patient transmission in the later cluster. A novel GES-5-encoding plasmid was present in K. oxytoca,E. coli and E. cloacae isolates from unlinked patients within the same hospital group and in human and wastewater isolates from three hospitals elsewhere in the UK.CONCLUSIONS: Genomic sequencing revolutionized the epidemiological understanding of the clusters, it also underlined the risk of covert plasmid propagation in healthcare settings and revealed the national distribution of the resistance-encoding plasmid. Sequencing results also informed and led to the ongoing use of enhanced diagnostic tests for detecting carbapenemases locally and nationally.